Organelle inheritance - what players have skin in the game? - Gruneberg, U; Barr, F (American Association for the Advancement of Science, 2017)
The concept of a checkpoint that monitors chromosome attachment to microtubules, and the discovery of the mitotic spindle assembly checkpoint proteins constituted a major milestone in understanding eukaryotic cell division (1). Chromosomes, however, are not the only constituents that have to be partitioned. Membrane-bound organelles such as the endoplasmic reticulum, Golgi apparatus, endosomes, and mitochondria are typically copied from existing structures, and it is necessary that both daughter cells receive a share of these components. On page 493 of this issue, Asare et al. (2) provide an exciting new view of organelle inheritance. The authors identify an organelle protein called peroxisomal biogenesis factor 11 beta (PEX11b) as a key determinant in the normal balance between dividing and differentiating cells in the mammalian epidermis. Of particular interest, reduced expression of PEX11b alters this balance, resulting in a thinning of the epidermis.